What do we know about the microbiome of I. ricinus? - Hodosi, Richard; Kazimirova, Maria; Soltys, Katarina (Frontiers in Cellular and Infection Microbiology, 2022)
Ixodes ricinus is an obligate hematophagous parasitic arthropod that is responsible for the transmission of a wide range of zoonotic pathogens including spirochetes of the genus Borrelia, Rickettsia spp., Coxiella burnetii, Anaplasma phagocytophilum and Francisella tularensis, which are part the tick´s microbiome. Most of the studies focus on “pathogens” and only very few elucidate the role of “non-pathogenic” symbiotic microorganisms in I. ricinus. While most of the members of the microbiome are leading an intracellular lifestyle, they are able to complement tick´s nutrition and stress response having a great impact on tick´s survival and transmission of pathogens. The composition of the tick´s microbiome is not consistent and can be tied to the environment, tick species, developmental stage, or specific organ or tissue. Ovarian tissue harbors a stable microbiome consisting mainly but not exclusively of endosymbiotic bacteria, while the microbiome of the digestive system is rather unstable, and together with salivary glands, is mostly comprised of pathogens. The most prevalent endosymbionts found in ticks are Rickettsia spp., Ricketsiella spp., Coxiella-like and Francisella-like endosymbionts, Spiroplasma spp. and Candidatus Midichloria spp. Since microorganisms can modify ticks’ behavior, such as mobility, feeding or saliva production, which results in increased survival rates, we aimed to elucidate the potential, tight relationship, and interaction between bacteria of the I. ricinus microbiome. Here we show that endosymbionts including Coxiella-like spp., can provide I. ricinus with different types of vitamin B (B2, B6, B7, B9) essential for eukaryotic organisms. Furthermore, we hypothesize that survival of Wolbachia spp., or the bacterial pathogen A. phagocytophilum can be supported by the tick itself since coinfection with symbiotic Spiroplasma ixodetis provides I. ricinus with complete metabolic pathway of folate biosynthesis necessary for DNA synthesis and cell division. Manipulation of tick´s endosymbiotic microbiome could present a perspective way of I. ricinus control and regulation of spread of emerging bacterial pathogens.